2018
DOI: 10.1002/ccr3.1696
|View full text |Cite
|
Sign up to set email alerts
|

HypervirulentKlebsiella pneumoniaeK1 liver abscess and endogenous endophthalmitis in a Caucasian man

Abstract: Key Clinical MessageInvasive Liver Abscess Syndrome is the most frequent of a number of infectious syndromes caused by hypervirulent Klebsiella pneumoniae clones. While incidences peak in Southeast Asia, travels to Asia and Asian ethnicity are independent risk factors for infection in the western countries, although non‐Asians are infected as well. Although challenging, a prompt diagnosis is of utmost importance to ensure adequate treatment and improve overall survival and visual outcome in cases with ocular i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Several case reports (5,23-32) and reviews (10,11,33-35) have described the clinical characteristics of EE secondary to PLA caused by K. pneumoniae . We showed the clinical characteristics in our patients and the previous reports (Table 3, 4).…”
Section: Discussionmentioning
confidence: 99%
“…Several case reports (5,23-32) and reviews (10,11,33-35) have described the clinical characteristics of EE secondary to PLA caused by K. pneumoniae . We showed the clinical characteristics in our patients and the previous reports (Table 3, 4).…”
Section: Discussionmentioning
confidence: 99%
“…Other manifestations include lumbar or cervical spondylitis and discitis, septic pulmonary emboli, lung abscesses, splenic abscesses, necrotizing fasciitis, neck abscesses, cerebral abscesses, purulent meningitis, otitis media, osteomyelitis, arthritis, prostate abscesses, pylephlebitis, and psoas muscle abscesses. [1012,1618] The outcome of some patients with K pneumoniae -induced endophthalmitis could be complete visual loss. [2,1012] Furthermore, severe K pneumoniae infection could result in death because of intracranial hypertension, cerebral hernia, and sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…[1012,1618] The outcome of some patients with K pneumoniae -induced endophthalmitis could be complete visual loss. [2,1012] Furthermore, severe K pneumoniae infection could result in death because of intracranial hypertension, cerebral hernia, and sepsis. [1,17] CT and enhanced CT scans are the best imaging examinations for discovering deep abscesses, especially those in the lungs, brain, pelvis, spine, and abdomen.…”
Section: Discussionmentioning
confidence: 99%
“…The first hypervirulent Kp endogenous endophthalmitis was reported in 1986 in Taiwan, in a patient with hepatic abscess without any underlying hepatobiliary pathology, raising attention about a new invasive strain [ 8 , 9 , 10 ]. Subsequent clinical trials reported that an epidemiologic shift in the epidemiology of cryptogenic liver abscess, with a growing number of case reports and subsequent clinical studies on larger patient groups signaling endemic growth of hvKp infections, accounting for 80% of cases in the Asian Pacific rim [ 11 , 12 , 13 , 14 , 15 , 16 , 17 ], and emerging in other regions such as the US, Australia, South Africa and recently in Europe [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ], characterized by a high rate of metastatic septic dissemination, endophthalmitis and CNS complications being among the most common.…”
Section: Introductionmentioning
confidence: 99%
“…Two plasmid-encoded virulence factors have been well characterized, rmpA, a regulator of mucoid phenotype that upregulates capsule synthesis, and the iron siderophores (aerobactin, yersiniabactin, salmochelin) which enable the bacterium to obtain iron essential for growing, by chelating the Fe-binding proteins of the host [ 40 , 41 , 42 , 43 , 44 , 45 ]. Other virulence factors include the chromosome-encoded virulence genes kfu/PTS, which codes for an iron uptake system (kfu) and a phosphoenolpyruvate, and allS gene, which is associated with the anaerobic metabolism of allantoin [ 21 , 39 , 41 ].…”
Section: Introductionmentioning
confidence: 99%